(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2025)
Helminthiasis is undoubtedly one of the most serious diseases that cause pathological processes in the human body. These parasitic infections, caused by helminths, significantly complicate the lives of the population, especially children, in countries with unfavorable sanitary conditions. Globally, more than 5 billion people suffer from various forms of helminthiasis, which highlights the scale of the problem. This study aims to investigate the causes, consequences, and strategies for combating helminthiasis, with a special focus on the situation in Uzbekistan. Our development is focused not only on examining the clinical aspects but also on studying the socio-economic consequences of helminthiasis, as well as various strategies and initiatives aimed at reducing their prevalence.